Rekonstruksi konsep manajemen pendidikan: tinjauan filosofis pragmatisme dalam menjawab tantangan revolusi industri 4.0 - azmi, arida ulul (Maliki Interdisciplinary Journal, 2026)
The Fourth Industrial Revolution demands education systems to become more adaptive, innovative, and responsive to technological advancements and 21st-century competency needs. However, educational management in Indonesia remains dominated by rigid and procedural bureaucracy, which slows technological adoption, limits curriculum creativity, and reduces teachers’ roles as innovators. This mismatch between the need for digital transformation and current managerial practices creates a gap in learning quality. In this context, Pragmatism offers a relevant philosophical foundation for reconstructing educational governance. Emphasizing the principles of inquiry, flexibility, evidence-based decision-making, and practical consequences, Pragmatism asserts that the value of a policy lies in its usefulness for improving students’ learning experiences. This article analyzes the relevance of Pragmatism in addressing bureaucratic weaknesses within Indonesian education and proposes a conceptual model of adaptive educational management suited to the digital era. The findings indicate that applying Pragmatic principles can restore the function of management as a problem-solving mechanism, encourage innovative autonomy for schools and teachers, and ensure that learning outcomes become the primary indicator of success. Thus, Pragmatism serves not merely as a philosophical theory but as an applicable managerial framework capable of responding effectively to the challenges of educational transformation in the era of Industry 4.0.